Maternal factors affecting foetal outcome in rural area of district Amritsar, Punjab - Kaur, Harpreet; Singh, Rana Ranjit; Sharma, Nishant (International Journal Of Community Medicine And Public Health, 2024)
Background: Birth weight not only indicates health of mother, nutrition and quality of life but also a pivotal factor in determining growth, survival and development of children. The key aspect influencing birth weight is maternal factors. Stress during pregnancy also affects a child’s growth and development. So the present study was planned to assess the maternal factors affecting foetal outcomes. The level of stress among antenatal women was also determined in the study. Methods: A prospective observational type of study was conducted from January to March, 2022. All the registered antenatal women were followed till outcome of pregnancy. Information was collected on predesigned and pretested proforma. Data analysis was done using SPSS version- 23. Results: A total of 114 antenatal were registered in rural field practice area under Department of Community Medicine, SGRDIMSAR, Amritsar. There were 108 singleton live births and 6 miscarriages among registered antenatal women. Almost half (47.2%) of subjects got their pregnancy registered before 12 weeks. Recommended more than minimum 4 antenatal visits were conducted in almost half (49.1%) of women. Three fourth (75.9%) women in first trimester of pregnancy were suffering from moderate stress while 24.1% women were suffering from low stress. Conclusions: In the present study maternal factors found to be significantly associated with birth weight of newborn were maternal age at first child, timing of 1st Antenatal visits, weight gain during pregnancy, number of Td (Tetanus diptheria) doses taken and consumption of IFA tablets. Perceived stress score (PSS) was also found to be significantly associated with birth weight of newborn.